If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation.
3x + 2y = −21
x − 3y = 4
A. 3(3y + 4) + 2y = −21
B. 3(−3y + 4) + 2y = −21
C. 3x + 2(3y + 4) = −21
D. 3x + 2(−3y + 4) = −21

Respuesta :

Answer:

Option A

Step-by-step explanation:

Step 1: Naming both equations:

[tex]Eq. 1: 3x + 2y=-21\\Eq. 2 : x-3y=4[/tex]

Step 2: Isolating x in Eq. 2

[tex]x=3y+4[/tex]

Step 3: Replacing x in Eq. 1

[tex]3(3y+4)+2y=-21[/tex]

Therefore, the answer is Option A